The Relationship Between Organizational Justice and Work Engagement : Trust as a Mediator - Sharma, Himani; Yadav, Reeta (Prabandhan: Indian Journal of Management, 2018)
Purpose : The purpose of this paper was to test the mediating impact of trust in organizational justice - work engagement relationship and to examine the association between organizational justice and work engagement in life insurance companies of Haryana. Design/Methodology/Approach : The study reported responses of 296 employees of public and private life insurance companies of Haryana. Data were collected on standardized questionnaire containing standard scales of distributive, procedural, interactional justice, trust, and work engagement. Mediation hypotheses were tested using Baron and Kenny’s (1986) recommendations. Findings : The results indicated that there was a strong and positive relationship among organizational justice, trust, and work engagement. Further, there was a significant impact of organizational justice on work engagement, and trust partially mediated the relationship between organizational justice and work engagement. Research Limitations/Implications : This paper used a cross - sectional research design in observing the relationship between organizational justice and work engagement with trust as a mediating variable. Data in the research paper were collected only from the insurance sector. Employees’ perceptions regarding fairness not only aroused trust, but also influenced work engagement levels. The results have implications for ensuring equity.